Experimental evaluation of thermal performance of cool pavement material using waste tiles in tropical climate - Nickholas, Anting; Mohd. Fadhil, Md. Din; Kenzo, Iwao; Mohanadoss, Ponraj; Karlvin, Jungan; Lee, Yee Yong; Lim, Alvin John Meng Siang (Elsevier Ltd, 2017)
Thermal performance are important parameter that represent the characteristic of cool pavement. The purpose of this paper is to present the findings on experimental result of thermal performance of the coating materials, which were developed from three types of waste tile aggregate, namely Full Body Porcelain (FBP), Monoporosa (MP) and Porcelain Glaze (PG). The samples were prepared based on the optimal design mix as proposed during optimization process based on surface temperature behavior of the samples. Experimental work was conducted in 24-h basis for continuously 14 days at actual tropical weather climate. The results showed that sample M1 with 100% of FBP provided the best result in terms of thermal performance, also the material was able to obtain highest surface temperature reduction up to 6.4 °C during peak period and solar reflectance of 0.49 at near infrared region. Statistical analysis shown that sample M4, 100% of PG tile aggregate, depicted a less desirable result due to its surface temperature reduction was not significant as compared with other investigated samples, which is only 4.32° during peak period. Overall result conclude that both material FBP and MP have a good potential to be used as cool pavement coating material based on its thermal and spectral performance. Thus, this study provides a useful information on the selection of tiles material that could be used as cool-pavement coatings, and contribute for a more potential measurement in mitigating urban heat island effects.